PENGARUH PARTISIPASI PENYUSUNAN ANGGARAN, KOMITMEN ORGANISASI DAN GAYA KEPEMIMPINAN TERHADAP KINERJA MANAJERIAL - Yunianto, Wisnu Tri; Hermanto, Suwardi Bambang (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2015)
The purpose of this research is to find out the influence of budgeting participation, organizationcommitment, and leadership style to the managerial performance at PT. Kereta Api Indonesia(Persero) Daerah Operasi 8 Surabaya. The research population is the managers and the employees whohave an authority in the process of budgeting at PT. Kereta Api Indonesia (Persero) Daerah Operasi 8Surabaya, and 63 people have been selected as the samples. The sample collection technique has beencarried out by using purposive sampling. The multiple linear regressions analysis is applied as theanalysis technique. The result of the test describes that the influence of budgeting participation,organization commitment, and leadership style variables to the managerial performance is significant.The result of regressions test describes that RÂ² = 0.668 or 66.8% of all variables i.e.: budgetingparticipation, organization commitment and leadership style simultaneously has influence to themanagerial performance. The result of this research has a limitation that the object of the research is onPT. Kereta Api Indonesia (Persero) Daerah Operasi 8 Surabaya so its generalization level is limited.Keywords: Budgeting Participation, Organization Commitment, Leadership Style, andManagerial Performance.